2014
DOI: 10.1002/pmic.201400145
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GnRH antagonist on endometrial protein profiles in the window of implantation

Abstract: GnRH antagonists can suppress luteinizing hormone and follicle-stimulating hormone (FSH), with less initial stimulatory effect and lower risk of ovarian hyperstimulation syndrome. The effects of GnRH antagonists on embryonic implantation remain controversial. To evaluate the effects of GnRH antagonists, endometrial tissues were biopsied from 12 women with intracytoplasmic sperm injection treatment, in which four subjects undergoing controlled ovulation stimulation with rFSH and GnRH antagonist, four subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…Thus far, no significant differences have been found between the two protocols with respect to the levels of specific biomarkers in follicular fluid, oocyte dysmorphisms, oocyte quality, and embryo quality8910. This indicates that endometrial receptivity, but not embryo quality, may be a factor contributing to the low pregnancy rates observed in patients treated with GnRH antagonist11. Recent findings have shown that the luteal phase single-dose GnRH agonist protocol can improve clinical outcomes after in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI), suggesting that the GnRH agonist may exert beneficial effects on the endometrium as endometrial epithelial and stromal cells express GnRH receptors (GnRHRs)1213.…”
mentioning
confidence: 95%
“…Thus far, no significant differences have been found between the two protocols with respect to the levels of specific biomarkers in follicular fluid, oocyte dysmorphisms, oocyte quality, and embryo quality8910. This indicates that endometrial receptivity, but not embryo quality, may be a factor contributing to the low pregnancy rates observed in patients treated with GnRH antagonist11. Recent findings have shown that the luteal phase single-dose GnRH agonist protocol can improve clinical outcomes after in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI), suggesting that the GnRH agonist may exert beneficial effects on the endometrium as endometrial epithelial and stromal cells express GnRH receptors (GnRHRs)1213.…”
mentioning
confidence: 95%
“…Five top significant canonical pathways are displayed along the xaxis. The threshold line corresponds to a P value of 0.05 [25]. All shown pathways are superior to the threshold [26].…”
Section: Discussionmentioning
confidence: 94%
“…For the ratio, taller bars have more proteins associated with the Canonical Pathway than shorter bars. The graph displaying the various pathways is presented from largest ratio to smallest ratio [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven proteins, including ACO2, CDC5L, GNAS, ARF1, ANPEP, SERPIND1 and SEC23B were differentially expressed exclusively in the GnRH antagonist group. According to the subsequent bioinformatic analysis, these proteins are mainly involved in angiogenesis, cell cycle, apoptosis, cell migration, cell proliferation and immune response (117).…”
Section: Proteomics and Endometrial Receptivitymentioning
confidence: 99%